THE EFFECT OF BRAND AWARENESS AND PRODUCT QUALITY ON CONSUMER LOYALTY TO JNC SNACK FOOD PRODUCTS COOKIES IN BANDUNG CITY - Define Haifa Rahmaeni; Ine Aprianti; Pupi Indriati Zaelani; Hersusetiyati Hersusetiyati (Multifinance, 2026)
JNCCookies faces challenges in maintaining revenue stability outside of seasonal periods. The  preliminary survey results indicate that consumer brand awareness of JNC Cookies is relatively low  and that the product quality has not fully met consumer satisfaction, thereby affecting consumer  loyalty.This study aims to analyze the influence of brand awareness and product quality on consumer  loyalty using a qualitative method quantified through a descriptive and verificative approach involving  100 respondents. The novelty of this research lies in its focus on the relationship between brand  awareness and product quality toward consumer loyalty at JNC Cookies, which has not been  extensively studied specifically within the handmade cookie industry in Bandung City.The findings  reveal that both brand awareness and product quality have a effect on consumer loyalty, both partially  and simultaneously. These results emphasize that both factors play an essential role in building long term consumer loyalty.Based on these findings, JNC Cookies is recommended to strengthen its  marketing strategies through more intensive promotions, building a strong brand identity, and creating  unique product characteristics that differentiate it from competitors in order to foster stronger and more  sustainable consumer loyalty.